War, Exile, and Cultural Resilience: Yu Dafu’s Sumatra Chinese Diaspora Experience: 战争、流亡与文化坚韧：郁达夫的苏门答腊华人流散经验 - Alpin Gadman Markali (Published by Confucius Institute UNS, 2025)
This study examines Yu Dafu’s Random Poems of War and Exile, composed during his wartime exile in Sumatra, to explore the experiences of the Chinese diaspora in Southeast Asia under the shadow of World War II. Through close reading and thematic analysis, the paper investigates how Yu’s poetry captures the physical and psychological trauma of war, the loneliness and alienation of life in a foreign land, deep attachments to homeland, and struggles of identity formation. It also highlights the role of intellectuals in preserving cultural traditions and exercising moral responsibility amid political turmoil. The findings suggest that Yu’s poetic work is not merely a personal record of exile but also a reflection of the collective hardships and spiritual state of the Chinese community in wartime Sumatra. By foregrounding themes of resilience and cultural survival, this study contributes to a deeper understanding of the Chinese diaspora’s historical experiences and offers new perspectives for diaspora literature studies. While limited by its focus on a single text, this research lays the groundwork for future interdisciplinary investigations that integrate broader historical sources and narratives of diaspora.